2009
DOI: 10.1007/s10888-009-9122-7
|View full text |Cite|
|
Sign up to set email alerts
|

Polarization and the decline of the middle class: Canada and the U.S.

Abstract: Several recent studies have suggested that the distribution of income (earnings, jobs) is becoming more polarized. Much of the evidence presented in support of this view consists of demonstrating that the population share in an arbitrarily chosen middle income class has fallen. However, such evidence can be criticized as being range-specific -depending on the particular cutoffs selected. In this paper we propose a range-free approach to measuring the middle class and polarization, based on partial orderings. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
245
0
17

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(263 citation statements)
references
References 9 publications
1
245
0
17
Order By: Relevance
“…In a later study, Foster and Wolfson (2010) also examined inequality of family disposable income in the United States and Canada in the 1980s. The authors concluded that inequality increased in the US from 1979 to 1986, while it decreased in Canada from 1981 to 1987.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a later study, Foster and Wolfson (2010) also examined inequality of family disposable income in the United States and Canada in the 1980s. The authors concluded that inequality increased in the US from 1979 to 1986, while it decreased in Canada from 1981 to 1987.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The issue has motivated a growing literature on the concept of polarisation. Love and Wolfson (1976) introduced the concept of polarisation between two social groups, which prompted the development of bi-polarisation measures such as those proposed in Foster and Wolfson (2010), and Wolfson (1994Wolfson ( , 1997. Ray (1994, 1999) and Duclos et al (2004) pioneered a different line of research focused on multi-group polarisation, and based on the concepts of within-group identification and between group alienation.…”
Section: Introductionmentioning
confidence: 99%
“…Ray (1994, 1999) and Duclos et al (2004) pioneered a different line of research focused on multi-group polarisation, and based on the concepts of within-group identification and between group alienation. 4 Within health economics, and following the strand of literature initiated by Foster and Wolfson (2010) and Allison and Foster (2004), Apouey (2007Apouey ( , 2010 proposed a specific measure of bi-polarisation for the case of self-assessed health. However, this is yet to find wide applicability in empirical work in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Since the initial work of Esteban and Ray (1994) and Foster andWolfson (1992 [2010]), different statistical measures have been proposed to analyse polarization. We will focus on those that have recently received more attention in empirical work.…”
Section: Measuring Polarization: Indicesmentioning
confidence: 99%